Terapi Zikir Untuk Meningkatkan Kesejahteraan Psikologis Penderita Hipertensi - Riska Prameswari; Qurotul Uyun; Indahria Sulistyarini (JIP (Jurnal Intervensi Psikologi), 2017)
This study aims to determine the influence of therapy of remembrance to improve the psychological wellbeing in patients with hypertension.The hypothesis of the study were there is difference in psychological well-being between the experimental group and control group. The subject involved in this study were 18 patients who experienced hypertension as well as having medium and low psychological well-being which divided into 2 groups: 9 people into experimental group and 9 people into control group. The experimental group was get the therapy of remembrance while the control group in the waiting list. The results of the data analysis with Mann Whitney shows that there are significant differences in psychological well-being between the experimental group and the control group, with the value of z= -3.587 (p<0.000). The group that get the therapy of remembrance experience an increase in psychological well-being which it possesses as compared with the control group. Keywords: Therapy of remembrance, psychological well-being, patient with hypertension